Committee on World War Veterans Legislation, House of Representatives. (U.S. Congressional Research., 1941)
Committee Print No. 32. Veterans Administration report on bill to authorize erection of an 800-bed veterans hospital for the southwest section of Georgia; cites similar bill from previous Congress.